CLINICAL-EPIDEMIOLOGICAL ASPECTS OF GASTRIC AND DUODENUM ULCER - A. B. Larichev; M. I. Maiorov; S. V. Favstov; A. G. Shalopiev (Вестник хирургии имени И.И. Грекова)
An analysis of reporting and statistical data showed the considerable changes in clinical-epidemiological indices of gastric and duodenum ulcer at the period from 1998 to 2012. The prevalence of the disease and the number of primary patients decreased in 2-3 times. The reduction of the rate of perforations and ulcerous bleeding had been observed. However, the authors noted, that a tendency of frequency of occurrence increased and efficacy indices reduced in the last years. The rate of postoperative lethality raised in the cases of perforated ulcer. On this basis, the authors recommend to reconsider the existing opinion about further extension of out-patient treatment of patients with given pathology.